Fuzzy logic and applications 9th International Workshop, WILF 2011, Trani, Italy, August 29-31,2011. Proceedings - Fanelli, Anna Maria; Pedrycz, Witold; Petrosino, Alfredo (LNCS sublibrary. SL 7, Artificial intelligence, 2011)
This book constitutes the refereed  proceedings of the 9th International Workshop on Fuzzy Logic and Applications, WILF 2011 held in Trani, Italy in August 2011. The 34 revised full papers presented were carefully reviewed and selected from 50 submissions. The papers are organized in topical sections on advances in theory of fuzzy sets, advances in fuzzy systems, advances in classification and clustering; and applications.